11x+1y=3

Simple and best practice solution for 11x+1y=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x+1y=3 equation:


Simplifying
11x + 1y = 3

Solving
11x + 1y = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1y' to each side of the equation.
11x + 1y + -1y = 3 + -1y

Combine like terms: 1y + -1y = 0
11x + 0 = 3 + -1y
11x = 3 + -1y

Divide each side by '11'.
x = 0.2727272727 + -0.09090909091y

Simplifying
x = 0.2727272727 + -0.09090909091y

See similar equations:

| 3m+9=5m-5 | | x+2*64=6*64 | | 10(x+1)=5x+25 | | 2(w+l)=2w+2l | | 3(x+20)=15 | | x/6-x/7=3/7 | | (a-16)/5=29 | | a-16/5=29 | | a-16/5=-8 | | 12x-18=10x | | 7(v-4)=14 | | (a-16)/5=-8 | | -6u+3=-3(u-3) | | 6sen(A)-3=0 | | -3m=-4+8 | | a^2+11a+10=0 | | (6d+5)(d-8)= | | X/5=12/35 | | 28x^2-94x+60=0 | | 28x^2-94x+30=0 | | (3c^2+2c-1)(2c^2+c+9)= | | xy-2a-2x+ay= | | 3x^2+9x-1= | | (3c+2c-1)(2c^2+c+9)= | | 3a^2+6a+2=0 | | 3u^3+15u^2-87u-315=0 | | -10.8/-2= | | 4+3(3a+3)=5 | | 0.01x-1.5=0.009 | | 3.14*R^2*12=258.75 | | pi*r^2*12=258.75 | | 1/10x-1/15=-1/6 |

Equations solver categories